Blood Profiles of Mithun (Bos Frontalis) under Different Stages of Reproduction - Perumal, P.; Vupru, K.; Khate, K.; Veeraselvam, M.; Verma, Atul Kumar; Nahak, A. K.; Rajkhowa, C. (International Journal of Bio-resource and Stress Management, 2014)
The study was carried out in the herd of mithun maintained at Jharnapani farm, NRC on Mithun, Nagaland. In total 64 (n=64) mithun of which, are divided in to four groups such as heifer (4), oestrus cows (4), pregnant cows (4) and non pregnant cows (4) for four strains namely Arunachalee (16), Mizoram (16), Nagaland (16) and Manipur (16) based on per rectal examination and farm records and were clinically normal. The blood samples were examined for the biochemical and heamatological profiles. Significant (p<0.05) difference was observed in ESR (mm/Hr) in pregnant and non pregnant stage between the different strains of mithun and also significant (p<0.05) difference was observed between the different stages of reproduction in Mizoram and Manipur strains. Results of bio-chemical parameters revealed that glucose concentration was showed a significant (p<0.05) different between the different strains in non pregnant stage of mithun. Other biochemical and haematological parameters were not significant different between the strains and between the different stages of reproduction.